Evaluation of the Efficiency of Recognition Radio Emitting Objects in Conjunction Signs Radar and Communication by Method of Statistical Tests - Bezruk, V.; Khriapkin, O.; Kaliuzhnyi, M.; Qiang, G.; Nikolaev, I. (IEEE, 2020)
In the report questions of assessment of efficiency of recognition of radio-emitting objects with use of set of signal signs both the systems of radiolocation, and communication systems and controls are considered. Results of experimental studies on the basis of these objects taking into account parameters of onboard radars and communication systems are provided.
Keywords: recognition; radio emitting; airborne radar; aircraft; radiation parameters; signaling signs